Barium titanate powder, its manufacturing method, and filler for sealing material

The method of producing barium titanate-based powders by jetting raw materials into a high-temperature field, followed by calcination and washing, effectively enhances the relative dielectric constant of the powders, addressing the challenge of varying dielectric constants across different particle sizes.

JP7667861B2Active Publication Date: 2025-04-23DENKA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023542365
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-20
Filing Date
2022-08-09
Publication Date
2025-04-23
Estimated Expiration
2042-08-09

AI Technical Summary

Technical Problem

There is a need for materials with higher dielectric constants, particularly for use in 5G mobile communication systems, as barium titanate-based powders tend to have varying dielectric constants depending on particle size, and existing methods do not effectively improve dielectric constants across different particle size ranges.

Method used

A method for producing barium titanate-based powders involves jetting a raw material into a high-temperature field, calcining the formed particles, and then washing and calcining the powder again to reduce the hollow area ratio of the particles, thereby enhancing the relative dielectric constant.

Benefits of technology

The resulting barium titanate-based powder exhibits an improved relative dielectric constant compared to conventional powders with similar particle sizes, achieving higher purity and dielectric performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667861000004
    Figure 0007667861000004
  • Figure 0007667861000005
    Figure 0007667861000005
  • Figure 0007667861000006
    Figure 0007667861000006
Patent Text Reader

Abstract

A method for producing a barium titanate-based powder, the method comprising: step a for forming barium titanate-based particles by spraying a material containing a barium titanate-based compound into a high temperature field heated to a temperature equal to or higher than the melting point of said compound; step b for rinsing a powder containing the barium titanate-based particles formed in step a, or for baking the powder containing the barium titanate-based particles formed in step a and then rinsing the powder after the baking; and step c for baking the rinsed powder obtained in step b.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a barium titanate powder and a method for producing the same, and a filler for an encapsulant. [Background technology]

[0002] Barium titanate compounds are known as materials with extremely high relative dielectric constants, and are widely used as fillers in various electronic component materials (eg, sealing materials) that require high dielectric constants.

[0003] Although the barium titanate compound itself has a high dielectric constant, the dielectric constant as a filler varies depending on the manufacturing method, and therefore various methods for manufacturing barium titanate powder with a high dielectric constant have been investigated.

[0004] For example, Patent Document 1 discloses a method for producing barium titanate powder by spraying a barium titanate raw material into a high-temperature flame, which produces barium titanate powder with a high relative dielectric constant. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-24925 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, there has been a demand for the development of materials with higher dielectric constants as materials compatible with millimeter waves used in fifth-generation (5G) mobile communication systems (e.g., fillers for sealing materials used in technologies such as antenna-in-package). Barium titanate powders tend to have higher dielectric constants as their particle size decreases, but the particle size range required varies depending on the application. Therefore, there is a demand for the development of technology that can improve the dielectric constant of barium titanate powders regardless of the particle size range.

[0007] The present disclosure has been made in consideration of the above circumstances, and has as its main object to provide a barium titanate-based powder having an improved relative dielectric constant compared to conventional barium titanate-based powders having a similar particle size, and a method for producing the same. [Means for solving the problem]

[0008] The present disclosure provides at least the following [1] to

[12] .

[0009] [1] A method for producing a barium titanate-based powder, comprising: a step a of forming barium titanate-based particles by injecting a raw material containing a barium titanate-based compound into a high-temperature field heated to a temperature equal to or higher than the melting point of the compound; a step b of washing the powder containing the barium titanate-based particles formed in the step a, or calcining the powder containing the barium titanate-based particles formed in the step a, and then washing the calcined powder; and a step c of calcining the washed powder obtained via the step b.

[0010] [2] The method further includes a step d of classifying the powder containing barium titanate-based particles formed in the step a to obtain a plurality of powders having different average particle sizes, and in the step b, among the plurality of powders obtained in the step d, a powder having an average particle size of 3.0 to 5.0 μm and a true specific gravity of 5.60 to 5.90 g / cm is selected. 3 The method for producing a barium titanate-based powder according to [1], wherein a powder containing barium titanate-based particles is formed in the step a.

[0011] [3] The method further includes a step d of classifying the powder containing barium titanate-based particles formed in the step a to obtain a plurality of powders having different average particle sizes, and in the step b, among the plurality of powders obtained in the step d, a powder having an average particle size of 9.0 to 12.0 μm and a true specific gravity of 5.60 to 5.90 g / cm is selected. 3 The method for producing a barium titanate-based powder according to [1], wherein a powder containing barium titanate-based particles is formed in the step a.

[0012] [4] The method for producing a barium titanate-based powder according to any one of [1] to [3], wherein in the step b, the powder containing the barium titanate-based particles formed in the step a is fired, and then the fired powder is washed.

[0013] [5] A powder containing barium titanate-based particles, wherein the barium titanate-based particles have a hollow area ratio of 5.0% or less in a cross section.

[0014] [6] The barium titanate powder according to [5], having an average particle size of 3.0 to 12.0 μm.

[0015] [7] A barium titanate powder according to [5] or [6], having an average sphericity of 0.80 or more.

[0016] [8] The average particle size is 3.0 to 5.0 μm and the BET specific surface area is 0.60 to 0.70 m 2 The barium titanate powder according to any one of [5] to [7], wherein the value is 0.01 to 0.25.

[0017] [9] The average particle size is 6.0 to 8.0 μm and the BET specific surface area is 0.40 to 0.50 m 2 The barium titanate powder according to any one of [5] to [7], wherein the value is 0.01 to 0.25.

[0018]

[10] The average particle size is 9.0 to 12.0 μm and the BET specific surface area is 0.25 to 0.30 m 2 The barium titanate powder according to any one of [5] to [7], wherein the value is 0.01 to 0.25.

[0019]

[11] The barium titanate-based powder according to any one of [5] to

[10] , wherein when 30 g of the powder is mixed with 142.5 mL of ion-exchanged water having an electrical conductivity of 1 μS / cm or less, and 7.5 mL of ethanol having a purity of 99.5% or more, the mixture is shaken for 10 minutes, and then allowed to stand for 30 minutes to prepare an extract, the extract has an electrical conductivity of 200 μS / cm or less.

[0020]

[12] A filler for an encapsulant, comprising the barium titanate powder according to any one of [5] to

[11] . Effect of the Invention

[0021] According to the present disclosure, a primary object is to provide a barium titanate-based powder having an improved relative dielectric constant as compared with conventional barium titanate-based powders having a comparable particle size, and a method for producing the same. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is an SEM image showing the surface of the barium titanate particle of Experimental Example 4. [Diagram 2] FIG. 2 is an SEM image showing the surface of the barium titanate particle of Experimental Example 6. [Diagram 3] FIG. 3 is an SEM image showing a cross section of a barium titanate particle of Experimental Example 4. [Figure 4] FIG. 4 is an SEM image showing a cross section of a barium titanate particle of Experimental Example 6. [Diagram 5] FIG. 5 is an SEM image showing barium titanate particles recognized by the autotrace tool. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] In this specification, a numerical range indicated using "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In addition, unless specifically stated otherwise, the units of the numerical values ​​described before and after "~" are the same. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage may be replaced with the upper limit or lower limit of a numerical range of another stage. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in an experimental example. In addition, the upper limit and lower limit values ​​described individually can be combined arbitrarily.

[0024] Hereinafter, several embodiments of the present disclosure will be described. However, the present disclosure is not limited to the following embodiments.

[0025] <Barium titanate powder> The barium titanate powder of one embodiment includes barium titanate particles having a hollow area ratio in a cross section (hereinafter simply referred to as "hollow area ratio") of 5.0% or less. Here, the barium titanate particles are particles containing a barium titanate compound as a main component, and the barium titanate powder is an aggregate of particles containing barium titanate particles as a main component. The "main component" refers to a component having the highest mass fraction among the constituent components (for example, a component having a mass fraction of more than 50 mass%).

[0026] Generally, perovskite oxides such as barium titanate have a crystal structure of ABO3. Both the A site and the B site are easily substituted with other elements, and it is possible to substitute different elements such as Nd, La, Ca, Sr, and Zr into the crystal structure. In this specification, in addition to barium titanate, compounds in which different elements are substituted at the A site and / or B site of barium titanate are collectively referred to as barium titanate-based compounds. Examples of barium titanate-based compounds include compounds represented by the following formula (1) and compounds represented by the following formula (2). (Ba (1-x) Ca x )(Ti (1-y) Zry )O3…(1) [In formula (1), x and y satisfy 0 ≦ x + y ≦ 0.4.] La x Ba (1-x) Ti (1-x / 4) O3…(2) [In formula (2), x satisfies 0 < x < 0.14.]

[0027] In a conventional barium titanate-based powder obtained by spraying a barium titanate-based raw material into a high-temperature flame, the barium titanate-based particles constituting the powder have a large number of spaces (hollow parts) inside. In contrast, the above barium titanate-based powder contains, as a main component, barium titanate-based particles with a hollow area ratio of 5.0% or less. Therefore, compared with the above conventional barium titanate-based powder having a similar particle size, it has a higher relative permittivity. This is presumably because the relative permittivity of the gas (for example, air) contained in the hollow part is smaller than that of the barium titanate-based compound, and the smaller the hollow area ratio, that is, the higher the ratio of the barium titanate-based compound in the whole particle, the higher the relative permittivity of the whole particle. Here, "having a similar particle size" means that, for example, the difference in the average particle diameter is within 1.0 μm.

[0028] The barium titanate-based particles may be substantially composed of a barium titanate-based compound. The barium titanate-based particles may contain components (impurities, etc.) other than the barium titanate-based compound. The content of the barium titanate-based compound may be 98 to 100% by mass, or may be 99 to 100% by mass, based on the total mass of the barium titanate-based particles.

[0029] The hollow area ratio of the barium titanate particles may be 4.7% or less, or 4.4% or less. The lower the hollow area ratio of the barium titanate particles, the easier it is to improve the relative dielectric constant. The hollow area ratio of the barium titanate particles may be, for example, 0.5% or more, 1.0% or more, 2.5% or more, 3.5% or more, or 4.0% or more. That is, the hollow area ratio of the barium titanate particles may be 0.5 to 5.0%, 1.0 to 4.7%, 2.5 to 4.4%, etc. The hollow area ratio is the ratio of the area of ​​the hollow parts present in the cross section (the total area of ​​all hollow parts) to the cross section area of ​​the barium titanate particles, and is calculated by determining the average particle diameter of the barium titanate particles, and then randomly selecting 30 barium titanate particles whose cross section diameter is within the range of the average particle diameter ±20% from the SEM image of the cross section of a resin molded product containing the barium titanate powder, and averaging the hollow area ratios of the selected 30 particles.

[0030] The extracted water electrical conductivity of the barium titanate powder may be 200 μS / cm or less, 100 μS / cm or less, or 70 μS / cm or less. Here, the extracted water electrical conductivity of the barium titanate powder means the electrical conductivity of a sample liquid (extracted water) prepared by mixing 30 g of barium titanate powder, 142.5 mL of ion-exchanged water with an electrical conductivity of 1 μS / cm or less, and 7.5 mL of ethanol with a purity of 99.5% or more, shaking for 10 minutes, and then leaving the mixture to stand for 30 minutes. The low extracted water electrical conductivity of the barium titanate powder means that the amount of ionic impurities contained in the barium titanate powder is small. The extracted water electrical conductivity is a value read after 1 minute by immersing an electrical conductivity cell in the sample liquid after standing, and the electrical conductivity of the ion-exchanged water is a value read after 1 minute by immersing an electrical conductivity cell in 150 mL of ion-exchanged water. The electrical conductivity can be measured using an electrical conductivity meter "CM-30R" and an electrical conductivity cell "CT-57101C" manufactured by DKK-TOA Corporation. The shaking in the extraction operation can be performed using a "Double Action Lab Shaker SRR-2" manufactured by AS ONE Corporation. In this embodiment, the electrical conductivity of the extracted water of the barium titanate particles may be within the above range.

[0031] The average particle diameter of the barium titanate powder may be 3.0 to 12.0 μm from the viewpoint of being suitably used as a filler for various electronic component materials, particularly for sealing materials that require a high relative dielectric constant. The average particle diameter of the barium titanate powder may be, for example, 3.0 to 5.0 μm, 6.0 to 8.0 μm, or 9.0 to 12.0 μm depending on the application. The average particle diameter of the barium titanate powder may be 3.2 μm or more or 3.5 μm or more, and 6.5 μm or less or 6.0 μm or less. The average particle diameter of the barium titanate powder may be 9.5 μm or more or 10.0 μm or more, and 11.8 μm or less or 11.5 μm or less. Here, the average particle diameter means a particle diameter (D50) at which the cumulative mass is 50% in a particle size distribution obtained by mass-based particle size measurement by a laser diffraction light scattering method. The average particle size can be measured using a Malvern Instruments Mastersizer 3000 equipped with a wet dispersion unit: Hydro MV. In this embodiment, the average particle size of the barium titanate particles may be within the above range.

[0032] The average sphericity of the barium titanate powder may be 0.80 or more, 0.83 or more, 0.85 or more, 0.86 or more, 0.87 or more, 0.88 or more, 0.89 or more, or 0.90 or more, from the viewpoint of facilitating the production of a material with a higher relative dielectric constant. The maximum value of the average sphericity is 1, and may be 0.99 or less, 0.97 or less, 0.95 or less, 0.93 or less, 0.91 or less, or 0.90 or less. The average sphericity may be, for example, 0.80 to 0.99, 0.83 to 0.97, 0.85 to 0.95, 0.86 to 0.93, 0.86 to 0.91, 0.86 to 0.90, 0.87 to 0.90, 0.88 to 0.90, 0.89 to 0.90, 0.90 to 0.93, etc. Here, the average sphericity means a value measured by the following method. First, the sample powder is mixed with ethanol to prepare a slurry with a concentration of the sample powder of 1% by mass, and the slurry is dispersed for 2 minutes at output level 8 using a Branson "SONIFIER450 (crushing horn 3 / 4" solid type). The obtained dispersed slurry is dropped onto a sample stage coated with carbon paste using a dropper. The dropped slurry is left on the sample stage in the air until it dries, and then osmium coating is performed. The resultant is photographed using a JEOL Ltd. scanning electron microscope "JSM-6301F type". The photograph is taken at a magnification of 3000 times, and an image with a resolution of 2048 x 1536 pixels is obtained. The obtained image is imported into a photographing computer, and the particles are recognized using the easy import tool using Mountec Co., Ltd.'s image analyzer "MacView Ver. 4", and the sphericity is measured from the particle's projected area (A) and perimeter (PM). If the area of ​​a perfect circle corresponding to the perimeter (PM) is (B), then the sphericity of the particle is A / B. If we assume a perfect circle (radius r) with the same perimeter as the perimeter (PM) of the sample, PM=2πr, B=πr 2 Therefore, B = π × (PM / 2π) 2 The sphericity (A / B) of each particle is A×4π / (PM) 2 The sphericity of 200 particles having a diameter equivalent to a circle of 2 μm or more in any projected area thus obtained is calculated, and the arithmetic mean value is defined as the average sphericity. In this embodiment, the average sphericity of the barium titanate particles may be within the above range.

[0033] The true specific gravity of barium titanate powder is 5.85 to 6.02 g / cm3 in order to obtain a higher relative dielectric constant. 3 The true specific gravity of the barium titanate powder may be 5.87 g / cm 3 More than 5.90g / cm 3 or more than 5.92g / cm 3 or more, 6.00 g / cm 3 Below, 5.98g / cm 3 Less than or equal to 5.97g / cm 3 The true specific gravity can be measured by Auto True Denser MAT-7000 manufactured by Seishin Enterprise Co., Ltd. In this embodiment, the true specific gravity of the barium titanate particles may be in the above range.

[0034] For example, when the average particle size of the barium titanate powder is 3.0 to 5.0 μm, the BET specific surface area is 0.60 to 0.70 m. 2 / g. A barium titanate powder having such a BET specific surface area tends to exhibit a higher relative dielectric constant. For example, when the average particle size of the barium titanate powder is 6.0 to 8.0 μm, the BET specific surface area is 0.40 to 0.50 m 2 / g. A barium titanate powder having such a BET specific surface area tends to exhibit a higher relative dielectric constant. For example, when the average particle size of the barium titanate powder is 9.0 to 12.0 μm, the BET specific surface area is 0.25 to 0.30 m 2 / g. Barium titanate powders having such a BET specific surface area tend to exhibit a higher dielectric constant. The BET specific surface area can be measured by a multipoint method using a fully automatic specific surface area measuring device and a He-N2 mixed gas as the measurement gas. In this embodiment, the BET specific surface area of ​​the barium titanate particles may be in the above range.

[0035] The barium titanate powder may be substantially composed of barium titanate particles. The barium titanate powder may contain components (impurities, etc.) other than the barium titanate particles. The content of the barium titanate particles in the barium titanate powder may be 98 to 100 mass % or 99 to 100 mass % based on the total mass of the barium titanate powder.

[0036] The barium titanate powder described above has a high relative dielectric constant, and therefore can be used in various electronic component materials, and is particularly suitable for use as a filler for sealing materials that require a high relative dielectric constant. In other words, another embodiment of the present disclosure is a filler for electronic component materials (preferably for sealing materials) that contains the barium titanate powder. Examples of sealing materials include sealing materials used in antenna-in-package. When using the barium titanate powder as a filler for sealing materials, it is also possible to use it by mixing it with other filler components.

[0037] <Method of manufacturing barium titanate powder> A method for producing a barium titanate-based powder in one embodiment includes a step a of forming barium titanate-based particles by injecting a raw material containing a barium titanate-based compound (barium titanate raw material) into a high-temperature field heated to a temperature equal to or higher than the melting point of the compound, a step b of washing the powder containing barium titanate-based particles formed in step a, or calcining the powder containing barium titanate-based particles formed in step a and then washing the calcined powder, and a step c of calcining the washed powder obtained via step b.

[0038] The above method may further include a step d of classifying the powder containing barium titanate-based particles formed in the above step a to obtain a plurality of powders having different average particle sizes. This step d may be performed after the step a and before the step b, or may be performed simultaneously with the step a. When the above method further includes the step d, in the step b, one of the plurality of powders obtained in the step d is used as the powder containing barium titanate-based particles formed in the step a. From the viewpoint of facilitating the production of the target barium titanate-based powder, the powder used in the step b has an average particle size of 3.0 to 5.0 μm and a true specific gravity of 5.60 to 5.90 g / cm. 3 The powder may have an average particle size of 9.0 to 12.0 μm and a true specific gravity of 5.60 to 5.90 g / cm 3 The powder may be a powder having a formula:

[0039] Hereinafter, each step (step a, step b, step c, and step d) in the method for producing a barium titanate powder will be described.

[0040] (Step a) In step a, a barium titanate raw material is injected into a high-temperature field to melt and solidify the raw material, forming barium titanate particles having a high degree of sphericity, and obtaining a powder containing the particles.

[0041] The raw material is a solid (e.g., particles) containing a barium titanate-based compound. The shape of the raw material is not particularly limited, and may be regular or irregular. The raw material may contain components other than the barium titanate-based compound (e.g., components such as impurities inevitably contained). The content of the barium titanate-based compound in the raw material may be 98 to 100 mass % or 99 to 100 mass % based on the total mass of the raw material.

[0042] The average particle size of the raw material may be 0.5 to 3.0 μm, or may be 1.0 to 2.5 μm or 1.5 to 2.0 μm. The larger the average particle size of the raw material, the larger the average particle size of the barium titanate particles obtained in step a, and the smaller the average particle size of the raw material, the smaller the average particle size of the barium titanate particles obtained in step a. When the average particle size of the raw material is within the above range, barium titanate particles having an average particle size of 3.0 to 5.0 μm are easily obtained in step a.

[0043] In step a, the raw material may be mixed with a solvent to form a slurry before use. That is, in step a, a slurry containing the raw material and the solvent may be sprayed into a high-temperature field. When the slurry is sprayed, the sphericity of the barium titanate particles is likely to be improved due to the surface tension of the solvent.

[0044] As the solvent, for example, water is used. As the solvent, organic solvents such as methanol and ethanol can also be used for the purpose of adjusting the calorific value. These may be used alone or in combination.

[0045] From the viewpoint of facilitating increasing the sphericity of the barium titanate particles, the concentration (content) of the raw material in the slurry may be 1 to 50 mass%, 20 to 47 mass%, or 40 to 45 mass% based on the total mass of the slurry.

[0046] The high-temperature field may be, for example, a high-temperature flame formed in a combustion furnace or the like. The high-temperature flame can be formed by a combustible gas and a combustion supporting gas. The temperature of the high-temperature field (for example, the high-temperature flame) is a temperature equal to or higher than the melting point of the barium titanate compound used as the raw material, for example, 1625 to 2000°C.

[0047] Examples of the flammable gas include propane, butane, propylene, acetylene, and hydrogen. These gases can be used alone or in combination of two or more. Examples of the combustion supporting gas include oxygen-containing gases such as oxygen gas. However, the flammable gas and the combustion supporting gas are not limited to these.

[0048] The injection (spray) of the raw material can be carried out, for example, using a two-fluid nozzle. The injection speed (feed rate) of the raw material may be 0.3 to 32 kg / h, or 9 to 29 kg / h, or 22 to 27 kg / h. When the injection speed of the raw material is within the above range, the sphericity of the barium titanate particles is likely to be improved. When a slurry is used, the injection speed of the raw material in the slurry may be within the above range.

[0049] A dispersion gas may be used when injecting the raw material. That is, the raw material (or a slurry containing the raw material) may be injected while being dispersed in the dispersion gas. This makes it easier to improve the sphericity of the barium titanate particles. As the dispersion gas, a combustion-supporting gas such as air or oxygen, or an inert gas such as nitrogen or argon can be used. A combustible gas can also be mixed into the inert gas in order to adjust the calorific value of the gas. The supply speed of the dispersion gas is set to 20 to 50 m / s from the viewpoint of facilitating the increase in the sphericity of the barium titanate particles. 3 / h, 30 to 47 m 3 / h or 40~45m 3 / h may also be used.

[0050] In the above step a, a powder substantially composed of barium titanate particles can be obtained. The obtained powder contains, for example, 98 to 100 mass % or 99 to 100 mass % of barium titanate particles. The barium titanate particles formed in the above step a may contain components other than the barium titanate compound (for example, components such as impurities inevitably contained). The content of the barium titanate compound in the barium titanate particles may be 98 to 100 mass % or 99 to 100 mass % based on the total mass of the barium titanate particles.

[0051] The sphericity of the barium titanate particles formed in the above step a (average sphericity of the powder containing barium titanate particles) is, for example, more than 0.70. In the above step a, the sphericity of the barium titanate particles (average sphericity of the powder containing barium titanate particles) can be 0.80 or more or 0.85 or more by adjusting the injection speed of the raw material, using a slurry, using a dispersion gas, etc. In addition, when carrying out the step d described below, it is also possible to further increase the sphericity by classification. The maximum value of the sphericity of the barium titanate particles (average sphericity of the powder containing barium titanate particles) is 1.

[0052] (Step d) In step d, the powder containing barium titanate particles formed in step a is classified. The classification method is not particularly limited, and may be screen classification or wind classification. From the viewpoint of efficient classification, a collection line may be directly connected to the lower part of the combustion furnace in which step a is performed, and the barium titanate particles in the combustion furnace may be sucked through the collection line by a blower installed behind the collection line (on the opposite side to the combustion furnace). The collection line may have a cyclone and a bag filter in addition to a heat exchanger connected to the combustion furnace. The heat exchanger, the cyclone and the bag filter may be connected in series in this order. In this case, the powder containing barium titanate particles is collected in each of the combustion furnace, the heat exchanger, the cyclone and the bag filter. The particle size of each powder to be collected can be adjusted, for example, by the suction amount of the blower.

[0053] When the above-mentioned collection line is used in step d, the powder collected on the upstream side (closer to the combustion furnace) tends to have a true specific gravity closer to that of the barium titanate-based compound. In the above-mentioned collection line, the true specific gravity of the powder collected by the heat exchanger and the true specific gravity of the powder collected by the cyclone are closest to that of the barium titanate-based compound, for example, 5.60 to 5.90 g / cm. 3 The true specific gravity of this powder is 5.60~5.80g / cm 3 , 5.65~5.78g / cm 3or 5.70~5.75g / cm 3 It is also possible to obtain such a true specific gravity. It is presumed that the reason why such a true specific gravity is obtained is that the more downstream (closer to the blower) the collected powder is, the more likely it is that impurities with low specific gravity (such as barium carbonate) are mixed in. The closer the true specific gravity of the powder is to the specific gravity of the barium titanate compound, the more likely it is that the effect of improving the relative dielectric constant by firing in steps b and c described below can be obtained. In addition, when the above-mentioned collection line is used in step d, the sphericity of the powder collected by the cyclone tends to be the highest.

[0054] In step d, the powder may be classified so that at least one of the obtained powders (powder containing barium titanate particles) has an average particle size of 5.0 μm or less. By using a powder having the above average particle size in step b, the cleaning effect in step b tends to be improved, and the effect of improving the relative dielectric constant by firing in steps b and c is more easily obtained. Powders having such an average particle size can be collected by a cyclone. The average particle size of the powder collected by the cyclone is, for example, 3.0 to 5.0 μm, and can also be 3.2 to 4.8 μm or 3.5 to 4.5 μm.

[0055] In step d, the powder may be classified so that at least one of the obtained powders (powder containing barium titanate particles) has an average particle size of 9.0 to 12.0 μm. Powders having such an average particle size can be collected by a heat exchanger. The average particle size of the powder collected by the heat exchanger can also be 9.5 to 11.8 μm or 10.0 to 11.5 μm.

[0056] (Step b) Step b is a step of washing the powder containing barium titanate particles formed in step a, or a step of calcining the powder containing barium titanate particles formed in step a and then washing the calcined powder. Although calcination before washing is an optional step, carrying out calcination tends to improve the effect of removing impurities by washing, and it is easy to obtain barium titanate powder with higher purity and higher dielectric constant.

[0057] As the powder containing barium titanate particles formed in step a, one of a plurality of powders obtained by classifying the powder containing barium titanate particles formed in step a may be used. That is, in step b, one of the powders obtained in step d may be used. When the above-mentioned collection line is used in step d, the cleaning effect tends to be improved when the powder collected by a cyclone is used, and the relative dielectric constant of the barium titanate powder obtained in step c tends to be further improved. From the viewpoint of obtaining high-purity barium titanate that contains as little other powders as possible, such as barium carbonate, the powder collected by a heat exchanger may be used.

[0058] The average particle size of the powder used in step b may be 5.0 μm or less, 4.8 μm or less, or 4.5 μm or less, from the viewpoint of easily improving the cleaning effect and the relative dielectric constant of the barium titanate powder. The average particle size of the powder used in step b may be 3.0 μm or more, 3.2 μm or more, or 3.5 μm or more, from the viewpoint of preventing aggregation and adhesion between particles during firing. From these viewpoints, the average particle size of the powder used in step b may be 3.0 to 5.0 μm, 3.2 to 4.8 μm, or 3.5 to 4.5 μm.

[0059] The average particle size of the powder used in step b may be 9.0 to 12.0 μm from the viewpoint of facilitating the production of high-purity spherical barium titanate. From the same viewpoint, the average particle size of the powder used in step b may be 9.5 μm or more or 10.0 μm or more, and may be 11.8 μm or less or 11.5 μm or less, or may be 9.5 to 11.8 μm or 10.0 to 11.5.

[0060] The true specific gravity of the powder used in step b is 5.60 to 5.90 g / cm from the viewpoint of making it easier to improve the relative dielectric constant of the obtained barium titanate powder. 3 and 5.60 to 5.80 g / cm 3 , 5.65~5.78g / cm 3 or 5.70~5.75g / cm 3The closer the true specific gravity of the powder used in step b is to the specific gravity of the barium titanate compound, the easier it is to obtain the effect of improving the relative dielectric constant by firing.

[0061] In view of the above, in one embodiment, the powder containing barium titanate particles used in step b has an average particle size of 3.0 to 5.0 μm and a true specific gravity of 5.60 to 5.90 g / cm 3 When the above-mentioned collection line is used in the step d, a powder having such an average particle size and true specific gravity can be easily obtained by collection in a cyclone (cyclone collection).

[0062] From the above viewpoint, in one embodiment, the powder containing barium titanate particles used in step b has an average particle size of 9.0 to 12.0 μm and a true specific gravity of 5.60 to 5.90 g / cm 3 When the above-mentioned collection line is used in the step d, a powder having such an average particle size and true specific gravity can be easily obtained by collection in a heat exchanger (heat exchanger collection).

[0063] The average sphericity of the powder used in step b may be 0.80 or more, or may be 0.82 or more, or may be 0.85 or more. The maximum value of the average sphericity is 1.

[0064] A firing furnace may be used for firing (heating) the powder. The firing temperature of the powder (for example, the temperature in the firing furnace) is, for example, 700°C or higher, and may be 800°C or higher, 900°C or higher, 1000°C or higher, or 1100°C or higher. The firing temperature of the powder is, for example, 1300°C or lower, and from the viewpoint of improving the sphericity, may be 1200°C or lower, 1100°C or lower, or 1000°C or lower. The firing temperature of the powder may be 800 to 1200°C or 900 to 1100°C from the viewpoint of easily improving the cleaning effect and more easily improving the relative dielectric constant of the barium titanate-based powder. The heating rate is not particularly limited, and may be 2 to 5°C / min, 2.5 to 4.5°C / min, or 3 to 4°C / min.

[0065] The firing time of the powder may be 2 hours or more, 4 hours or more, or 6 hours or more from the viewpoint of improving the cleaning effect and the relative dielectric constant of the barium titanate powder. If the firing time of the powder is 6 hours or more, the tendency of improving the cleaning effect and the relative dielectric constant becomes small, so from the viewpoint of production efficiency, the firing time of the powder may be 8 hours or less. Note that the firing time does not include the temperature rise time.

[0066] The cooling conditions after firing are not particularly limited. Cooling after firing may be natural cooling in a furnace.

[0067] The washing is carried out by contacting the powder containing the barium titanate particles formed in step a or the powder after firing (hereinafter, these are collectively referred to as "powder to be washed") with a washing liquid. As the powder after firing, the powder obtained by the above firing may be used as it is, or a powder obtained by subjecting the powder obtained by the above firing to a treatment such as classification may be used. The washing may be carried out, for example, by putting the powder to be washed in the washing liquid and stirring. In this case, the temperature of the washing liquid may be 10 to 25°C. Stirring may be carried out using, for example, a stirrer, a magnetic stirrer, a disperser, or the like. The stirring time may be 5 to 30 minutes. The stirring speed may be 200 to 400 rpm.

[0068] The cleaning liquid is capable of dissolving and removing impurities (particularly ionic impurities) generated during the production of barium titanate particles. For example, an aqueous cleaning liquid is used as such a cleaning liquid. The aqueous cleaning liquid is a cleaning liquid containing water as a main component. The content of water in the aqueous cleaning liquid may be 60 to 100 mass%, 70 to 100 mass%, or 80 to 100 mass% based on the total mass of the aqueous cleaning liquid. The aqueous cleaning liquid may be composed of only water (e.g., pure water) or may contain other components. Examples of other components include ethanol and acetone. Note that the cleaning liquid does not need to contain water as long as the above impurities can be removed. For example, a cleaning liquid containing a component capable of dissolving barium carbonate (e.g., ethanol, acetone, hydrogen chloride, nitric acid, etc.) and not containing water can be used as the cleaning liquid.

[0069] From the viewpoint of easily obtaining a cleaning effect, the amount of the powder to be cleaned brought into contact with the cleaning liquid may be 10 to 40 parts by mass, 15 to 35 parts by mass, or 20 to 30 parts by mass, relative to 100 parts by mass of the cleaning liquid. Note that the above amount is the amount of the powder to be cleaned brought into contact with the cleaning liquid per cleaning.

[0070] The washing may be repeated several times. For example, the washing may be performed by putting the powder to be washed into the washing liquid, stirring, allowing the powder to settle, removing the supernatant, and adding the washing liquid again and stirring. Further high purity can be achieved by increasing the number of washings. The number of washings may be two or more, or may be three or more. The number of washings may be ten or less, or may be five or less. The smaller the number of washings, the higher the relative dielectric constant of the obtained barium titanate-based powder tends to be. When firing is performed before washing, ionic impurities can be sufficiently removed with fewer washings.

[0071] In step b, the washed powder may be dried. The drying conditions may be any conditions that can sufficiently dry the washed barium titanate particles (barium titanate powder). The drying temperature may be 100 to 110° C. The drying time may be 12 to 24 hours.

[0072] (Step c) In step c, the washed powder obtained through step b is fired. The washed powder is the powder obtained through the above washing treatment, and may be the powder after the above drying treatment.

[0073] The powder may be fired in the same manner as in step b, and the firing temperature, heating rate, and firing time may be adjusted within the ranges exemplified in step b. The firing temperature of the powder (for example, the temperature in a firing furnace) may be 800 to 1200°C or 900 to 1100°C, from the viewpoint of making it easier to reduce the proportion of hollow spaces and to obtain a higher relative dielectric constant.

[0074] According to the above-described method for producing a barium titanate powder, a barium titanate powder having a higher relative dielectric constant can be obtained. Specifically, a powder (barium titanate powder) containing barium titanate particles with a small hollow area ratio in cross section can be obtained. The hollow area ratio of the barium titanate particles in the barium titanate powder obtained by the above-described method is, for example, 5.0% or less, and can also be 4.7% or less or 4.4% or less.

[0075] Furthermore, the barium titanate powder obtained by the above method has high purity. Specifically, the extracted water electrical conductivity of the barium titanate powder produced by the above method is, for example, 200 μS / cm or less. The extracted water electrical conductivity of the barium titanate powder can be further reduced by increasing the number of washings, and can also be 100 μS / cm or less or 70 μS / cm or less.

[0076] The reason why the above method can provide a barium titanate powder having high purity and an improved relative dielectric constant is not clear, but is presumed to be as follows.

[0077] It has been confirmed by the inventors of the present disclosure that when the barium titanate particles obtained in step a are fired at high temperatures, the ratio of hollow parts in the barium titanate particles is reduced, and the dielectric constant is improved. However, since the barium titanate particles obtained in step a contain impurities, when the impurities are removed by washing, hollow parts are generated in the area where the impurities were present. Therefore, even if firing is performed, if washing is performed thereafter, the dielectric constant is reduced due to the increase in hollow parts. In contrast, in the above method, since firing is performed after washing, the hollow parts generated by washing are reduced, and the ratio of hollow parts in the barium titanate particles is reduced. In addition, since impurities also have an adverse effect on the dielectric constant, the above method can improve the dielectric constant compared to a method in which washing is not performed. It is presumed that the above effect is obtained for these reasons.

[0078] The barium titanate powder obtained by the above method tends to have a high sphericity. The average sphericity of the barium titanate powder obtained by the above method is, for example, 0.80 or more, and can be 0.83 or more, 0.85 or more, 0.86 or more, 0.87 or more, 0.88 or more, 0.89 or more, or 0.90 or more. The maximum value of the average sphericity is 1, but the above method can obtain a barium titanate powder with an average sphericity close to 1 (for example, 0.80 to 0.99, 0.83 to 0.97, 0.85 to 0.95, 0.86 to 0.93, 0.86 to 0.91, 0.86 to 0.90, 0.87 to 0.90, 0.88 to 0.90, 0.89 to 0.90, 0.90 to 0.93, etc.).

[0079] The barium titanate powder obtained by the above method tends to have a true specific gravity close to the specific gravity of the barium titanate compound. The true specific gravity of the barium titanate powder obtained by the above method is, for example, 5.85 to 6.02 g / cm 3 and 5.87-6.00g / cm 3 , 5.90~5.98g / cm 3 , 5.92~6.00g / cm 3 , 5.92~5.98g / cm 3 or 5.92~5.97g / cm 3It can also be done like this.

[0080] The average particle diameter of the barium titanate powder obtained by the above method is, for example, 3.0 to 12.0 μm. In step b, when a powder having an average particle diameter of 3.0 to 5.0 μm (for example, a powder collected by a cyclone) is used among the multiple powders obtained in step d, a barium titanate powder having an average particle diameter of 3.0 to 5.0 μm can be obtained. In addition, in step b, when a powder having an average particle diameter of 9.0 to 12.0 μm (for example, a powder collected by a heat exchanger) is used among the multiple powders obtained in step d, a barium titanate powder having an average particle diameter of 9.0 to 12.0 μm can be obtained. The average particle diameter of the barium titanate powder can be 3.2 μm or more or 3.5 μm or more, and can be 6.5 μm or less or 6.0 μm or less. The average particle size of the barium titanate powder can be 9.5 μm or more, or 10.0 μm or more, and can be 11.8 μm or less, or 11.5 μm or less.

[0081] The average particle size can also be adjusted by combining multiple barium titanate powders obtained by the above method. For example, a barium titanate powder obtained in step b using a powder having an average particle size of 3.0 to 5.0 μm (e.g., powder collected by a cyclone) and a barium titanate powder obtained in step b using a powder having an average particle size of 9.0 to 12.0 μm (e.g., powder collected by a heat exchanger) can be combined to obtain a barium titanate powder. The average particle size of the barium titanate powder obtained in this way is, for example, 6.0 to 8.0 μm.

[0082] In the above method, the particles are sintered to have a dense structure, so the BET specific surface area of ​​the barium titanate powder obtained by the above method tends to be smaller than the specific surface area of ​​the barium titanate powder obtained by other methods. Specifically, for example, under conditions where the average particle size is 3.0 to 5.0 μm, the BET specific surface area is 0.60 to 0.70 m 2For example, under the condition that the average particle size is 9.0 to 12.0 μm, a barium titanate powder having a BET specific surface area of ​​0.25 to 0.30 m can be obtained. 2 As described above, when a plurality of barium titanate powders are combined to obtain an average particle size of 6.0 to 8.0 μm, a barium titanate powder having a BET specific surface area of ​​0.40 to 0.50 m can be obtained. 2 A barium titanate powder having a molecular weight of 1000 to 1500 g can be obtained. EXAMPLES

[0083] The contents of the present disclosure will be described in more detail below using experimental examples, but the present disclosure is not limited to the following experimental examples.

[0084] <Experimental Examples 1-2> (Preparation of ingredients) As a raw material, "BT-SA" (product name, barium titanate powder, average particle size: 1.6 μm) manufactured by Kyoritsu Material Co., Ltd. was prepared and mixed with water to prepare a slurry (BT-SA concentration: 43% by mass).

[0085] (Step a: Formation of barium titanate particles) An apparatus was prepared that included a combustion furnace with a double-tube LPG-oxygen mixed burner capable of forming an inner flame and an outer flame installed at the top, a collection line directly connected to the bottom of the combustion furnace, and a blower connected to the collection line. The collection line had a heat exchanger connected to the combustion furnace, a cyclone connected to the top of the heat exchanger, and a bag filter connected to the top of the cyclone, and the bag filter was connected to the blower.

[0086] A high-temperature flame (temperature: about 2000°C) was formed in the combustion furnace of the above equipment, and the above slurry was fed from the center of the burner at a feed rate of 37 L / Hr (25 kg / h in BT-SA equivalent) with carrier air (feed rate: 40 to 45 m 3 The flame was formed by providing several tens of fine holes at the outlet of a double-tube burner, through which LPG (supply rate 17 m 3 / h) and oxygen (supply rate 90m 3 The method was carried out by injecting a mixed gas of barium titanate and argon gas (1000 / h) into the nozzle. This resulted in the formation of spherical barium titanate particles.

[0087] (Step d: Classification of powder containing barium titanate particles) The powder containing barium titanate particles formed in the combustion furnace was sucked in by a blower, and the powder containing barium titanate particles was collected in each of the combustion furnace, the heat exchanger, the cyclone, and the bag filter. Of the collected powders, the powder collected in the heat exchanger (heat exchange product) was used as the barium titanate powder of Experimental Example 1, and the powder collected in the cyclone (CY product) was used as the barium titanate powder of Experimental Example 2.

[0088] (Measurement of true specific gravity) The true specific gravity of the barium titanate powder obtained in Experimental Examples 1 and 2 was measured using an Auto True Denser MAT-7000 manufactured by Seishin Enterprise Co., Ltd. The results are shown in Table 1.

[0089] (Mean Sphericity Measurement) The average sphericity of the barium titanate powder obtained in Experimental Examples 1 and 2 was measured by the following method. First, the barium titanate powder was mixed with ethanol to prepare a slurry with a barium titanate powder concentration of 1% by mass, and the slurry was dispersed for 2 minutes at output level 8 using a BRANSON SONIFIER450 (crushing horn 3 / 4” solid type). The obtained dispersed slurry was dropped onto a sample stage coated with carbon paste using a dropper. The dropped slurry was left to stand in the air on the sample stage until it dried, and then osmium coating was performed. The result was photographed with a JEOL Ltd. scanning electron microscope JSM-6301F. The photograph was taken at a magnification of 3000 times, and an image with a resolution of 2048 × 1536 pixels was obtained. The obtained image was imported into a computer and the particles were recognized using an image analyzer MacView Ver. 4 manufactured by Mountec Co., Ltd., using a simple import tool. From the projected area (A) and perimeter (PM) of a particle, the sphericity of 200 particles with an equivalent circle diameter of 2 μm or more for any projected area was calculated, and the average value was taken as the average sphericity. The results are shown in Table 1.

[0090] (Measurement of average particle size) The average particle size (D50) of the barium titanate powder obtained in Experimental Examples 1 and 2 was determined by mass-based particle size measurement by laser diffraction light scattering method using Malvern's "Mastersizer 3000, wet dispersion unit: Hydro MV installed". In the measurement, the barium titanate powder was mixed with water, and the mixture was dispersed for 2 minutes as a pretreatment by applying 200W output using Tommy Seiko's "Ultrasonic Generator UD-200 (with micro tip TP-040 installed)", and the mixture after dispersion was dropped into the dispersion unit so that the laser scattering intensity was 10 to 15%. The stirring speed of the dispersion unit stirrer was 1750 rpm, and ultrasonic mode was not used. The particle size distribution was analyzed by dividing the particle size range of 0.01 to 3500 μm into 100 parts. The refractive index of water was 1.33, and the refractive index of barium titanate was 2.40. The results are shown in Table 1.

[0091] (Measurement of electrical conductivity of extracted water) The electric conductivity of the extracted water of the barium titanate powder obtained in Experimental Examples 1 and 2 was measured by the following method. First, 30 g of barium titanate powder was put into a 300 mL polyethylene container, and then 142.5 mL of ion-exchanged water with an electric conductivity of 1 μS / cm or less and 7.5 mL of ethanol with a purity of 99.5% or more were added. Next, the obtained mixed liquid was shaken by a reciprocal shaking method for 10 minutes using a "Double Action Lab Shaker SRR-2" manufactured by AS ONE Corporation, and then left to stand for 30 minutes to prepare a sample liquid (extracted water). An electric conductivity cell was immersed in the sample liquid after standing, and the value was read after 1 minute, and this was used as the electric conductivity of the extracted water. The electric conductivity of the ion-exchanged water was measured by immersing an electric conductivity cell in 150 mL of ion-exchanged water and reading the value after 1 minute. In addition, an electric conductivity meter "CM-30R" and an electric conductivity cell "CT-57101C" manufactured by DKK-TOA Corporation were used to measure the electric conductivity. The results are shown in Table 1.

[0092] (BET specific surface area measurement) The BET specific surface area of ​​the barium titanate powder obtained in Experimental Examples 1 and 2 was measured by the following method. First, 4 g of barium titanate powder was filled into an empty cell, and degassing was performed in an environment of 300°C. After degassing, the cell filled with the barium titanate powder was set in a fully automatic specific surface area measuring device "Macsorb Model 1208" manufactured by Mountech Co., Ltd., and the specific surface area was measured. He-N2 mixed gas was used as the measurement gas, and the measurement was performed by the multipoint method with a main flow rate of 25 mL / min. The results are shown in Table 1.

[0093] (Evaluation of relative dielectric constant) Resin compositions were prepared using the barium titanate powders obtained in Experimental Examples 1 and 2, respectively, and the effect of the barium titanate powder in improving the relative dielectric constant was evaluated based on the relative dielectric constant of the cured product of the resin composition (cured resin product). Specifically, first, 95.4 g of barium titanate powder, 11.1 g of epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "jER-807" ("jER" is a registered trademark)), 3.3 g of phenol-based curing agent (manufactured by Meiwa Chemical Industry Co., Ltd., product name "MEH-8005"), 0.15 g of imidazole-based curing agent (manufactured by Shikoku Chemical Industry Co., Ltd., product name "2PHZ-PW"), 0.15 g of catalyst (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product name "triphenylphosphine"), 0.3 g of release agent (manufactured by Clariant Japan Co., Ltd., "LICOWAX E" ("LICOWAX" is a registered trademark)), and 0.15 g of surface treatment agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403") were mixed to obtain a resin composition. The resin composition thus obtained was then poured into a silicon tube having an inner diameter of 25 mm and allowed to stand for 10 hours in an atmosphere at 120°C to cure, thereby obtaining an evaluation sample made of a cured resin. The relative dielectric constant of the obtained evaluation sample was measured by a capacitance method using a dielectric constant measuring instrument "E4980A Precision LCR Meter" manufactured by KEYSIGHT TECHNOLOGIES. The results are shown in Table 1.

[0094] [Table 1]

[0095] <Experimental Example 3> In the same manner as in Experimental Examples 1 and 2, step a (formation of barium titanate particles) and step d (classification of powder containing barium titanate particles) were carried out, and then the powder (heat exchanged product) collected in the heat exchanger was subjected to the firing step (step b1) and washing step (step b2) described below as step b.

[0096] (Step b1: Firing step) 8 kg of the powder collected in the heat exchanger was packed into a mullite scabbard, heated to 1000°C at a heating rate of 3.3°C / min, and then fired at 1000°C for 6 hours to obtain a fired product. Cooling after firing was carried out by natural cooling in the furnace.

[0097] (Process b2: Washing process) The fired product (fired powder) obtained in step b1 was repeatedly washed with water five times. The washing operation consisted of adding 2 L of pure water (20°C) to 500 g of powder, stirring at 300 rpm for 10 minutes, leaving it to stand for 30 minutes to allow the powder to settle, and removing the supernatant liquid with a tube pump. After the washing operation, the powder obtained was thoroughly dried at 110°C.

[0098] By the above operations, a barium titanate powder of Experimental Example 3 was obtained. Next, the true specific gravity, average sphericity, average particle size, extracted water electrical conductivity, and BET specific surface area of ​​the obtained barium titanate powder were measured, and the relative dielectric constant was evaluated, in the same manner as in Experimental Examples 1 and 2. The results are shown in Table 2.

[0099] <Experimental Example 4> Except for using powder collected in a cyclone (CY product) instead of powder collected in a heat exchanger (heat exchange product), step b1 (firing step) and step b2 (washing step) were carried out in the same manner as in Experimental Example 3 to obtain barium titanate powder of Experimental Example 4. Next, the true specific gravity, average sphericity, average particle size, extracted water electrical conductivity, and BET specific surface area of ​​the obtained barium titanate powder were measured in the same manner as in Experimental Examples 1 and 2, and the relative dielectric constant was evaluated. The results are shown in Table 2.

[0100] <Experimental Example 5> In the same manner as in Experimental Examples 1 and 2, step a (formation of barium titanate particles) and step d (classification of powder containing barium titanate particles) were carried out, and then step b1 (firing step) and step b2 (washing step) were carried out on the powder (heat exchange product) collected in the heat exchanger in the same manner as in Experimental Example 3. That is, in this Experimental Example, in step b1, the average particle size was 9.0 to 12.0 μm and the true specific gravity was 5.60 to 5.90 g / cm. 3 The powder was used. Thereafter, the obtained dry powder was subjected to a firing step (second firing step) as step c. Specifically, 8 kg of the dry powder was packed into a mullite scabbard, heated to 1000°C at a heating rate of 3.3°C / min, and then fired at 1000°C for 6 hours. This resulted in the barium titanate powder of Experimental Example 5. Note that cooling after firing in step c was performed by natural cooling in a furnace. Next, the true specific gravity, average sphericity, average particle size, extracted water electrical conductivity, and BET specific surface area of ​​the obtained barium titanate powder were measured in the same manner as in Experimental Examples 1 and 2, and the relative dielectric constant was evaluated. The results are shown in Table 2.

[0101] <Experimental Example 6> In the same manner as in Experimental Examples 1 and 2, step a (formation of barium titanate particles) and step d (classification of powder containing barium titanate particles) were carried out, and then step b1 (firing step) and step b2 (washing step) were carried out on the powder (CY product) collected in a cyclone in the same manner as in Experimental Example 4. That is, in this Experimental Example, in step b1, the powder had an average particle size of 3.0 to 5.0 μm and a true specific gravity of 5.60 to 5.90 g / cm. 3 The powder was used. Next, the obtained dry powder was subjected to step c (second firing step) in the same manner as in Experimental Example 5 to obtain a barium titanate powder of Experimental Example 6. Next, the true specific gravity, average sphericity, average particle size, extracted water electrical conductivity, and BET specific surface area of ​​the obtained barium titanate powder were measured in the same manner as in Experimental Examples 1 and 2, and the relative dielectric constant was evaluated. The results are shown in Table 2.

[0102] <Experimental Example 7> A barium titanate powder of Experimental Example 7 was obtained in the same manner as in Experimental Example 5, except that step b1 (firing step) was not performed. Next, the true specific gravity, average sphericity, average particle size, extracted water electrical conductivity, and BET specific surface area of ​​the obtained barium titanate powder were measured, and the relative dielectric constant was evaluated, in the same manner as in Experimental Examples 1 and 2. The results are shown in Table 2.

[0103] <Experimental Example 8> The barium titanate powder of Experimental Example 5 and the barium titanate powder of Experimental Example 6 were mixed in a mass ratio of 6:4 to obtain a barium titanate powder of Experimental Example 8. Next, the true specific gravity, average sphericity, average particle size, extracted water electrical conductivity, and BET specific surface area of ​​the obtained barium titanate powder were measured, and the relative dielectric constant was evaluated, in the same manner as in Experimental Examples 1 and 2. The results are shown in Table 3.

[0104] <Experimental Example 9> The barium titanate powder of Experimental Example 3 and the barium titanate powder of Experimental Example 4 were mixed in a mass ratio of 6:4 to obtain a barium titanate powder of Experimental Example 9. Next, the true specific gravity, average sphericity, average particle size, extracted water electrical conductivity, and BET specific surface area of ​​the obtained barium titanate powder were measured, and the relative dielectric constant was evaluated, in the same manner as in Experimental Examples 1 and 2. The results are shown in Table 3.

[0105] <Analysis and Evaluation> [Observation of surface condition] Barium titanate particles were taken out from the barium titanate particles of Experimental Example 4 and the barium titanate powder of Experimental Example 6, and observed with a scanning electron microscope (SEM) to obtain surface SEM images. The obtained surface SEM images are shown in Figures 1 and 2. Figure 1 is a surface SEM image of the barium titanate particles of Experimental Example 4, and Figure 2 is a surface SEM image of the barium titanate particles of Experimental Example 6. It was confirmed from Figures 1 and 2 that there were fewer voids present on the particle surfaces in Experimental Example 6 compared to Experimental Example 4.

[0106] [Observation of cross-section] The cross sections of the barium titanate particles of Experimental Example 4 and the barium titanate particles of Experimental Example 6 were observed. Specifically, first, 0.1 g of barium titanate powder was embedded in 0.3 g of epoxy resin "G2" manufactured by Gatan. Next, degassing treatment was performed at 90°C for 90 minutes, and then the epoxy resin was cured by heating at 130°C for 30 minutes to obtain a resin molded body containing barium titanate powder. At this time, the size of the resin molded body was about 5 mm x 10 mm x 3 mm. After curing, the resin surface was polished with SiC paper to perform surface preparation, and milling was performed using an ion milling device (product name "IM4000Plus") manufactured by Hitachi High-Tech Corporation. Then, osmium coating treatment was performed using an osmium coater (product name "HPC-20") manufactured by Vacuum Device Co., Ltd. Next, the coated surface was observed with a scanning electron microscope (SEM) to obtain a cross-sectional SEM image. The obtained cross-sectional SEM image is shown in Figures 3 and 4. Fig. 3 is a cross-sectional SEM image of the barium titanate particles of Experimental Example 4, and Fig. 4 is a cross-sectional SEM image of the barium titanate particles of Experimental Example 6. From Figs. 3 and 4, it was confirmed that, compared with Experimental Example 4, there were fewer voids (hollow portions) present in the cross section of the particles in Experimental Example 6, and solid particles were formed.

[0107] [Measurement of hollow area ratio] Using the cross-sectional SEM images obtained by the above cross-sectional observation, the hollow area ratios in the cross sections of the particles of the barium titanate powders of Experimental Examples 3 to 9 were measured. Specifically, the cross-sectional SEM images were first imported into the image analysis software "ImagePRO", and as shown in FIG. 5, the particles were recognized using an automatic trace tool, and the brightness range was set to 0-150 from the binarization tool window, and the cross-sectional area of ​​the particles and the area of ​​the hollow parts present in the cross sections (total area of ​​all hollow parts) were measured. The measurement was performed on the 30 particles that were randomly selected from multiple cross-sectional SEM images and had a cross-sectional diameter within the range of ±20% of the average particle diameter measured above. Next, the hollow area ratios in the cross sections of each particle ([total area of ​​hollow parts / cross-sectional area of ​​particle] × 100) were calculated from the measured values. The average hollow area ratios of the obtained 30 particles were calculated, and this was taken as the hollow area ratio of the barium titanate particles. The results are shown in Tables 2 to 3.

[0108] [Table 2]

[0109] [Table 3]

[0110] In Experimental Examples 5 and 7, the hollow area ratio of the particles was lower than that of Experimental Example 3 in which a barium titanate powder having a similar average particle size was obtained, and a resin cured product with a higher dielectric constant was obtained. Similarly, in Experimental Example 6, the hollow area ratio of the particles was lower than that of Experimental Example 4 in which a barium titanate powder having a similar average particle size was obtained, and a resin cured product with a higher dielectric constant was obtained. Similarly, in Experimental Example 8, the hollow area ratio of the particles was lower than that of Experimental Example 9 in which a barium titanate powder having a similar average particle size was obtained, and a resin cured product with a higher dielectric constant was obtained. From these findings, it was confirmed that regardless of the particle size range of the powder to be treated, the hollow area ratio of the particles was reduced and the dielectric constant of the powder was improved by performing baking after washing.

Claims

1. A step a of forming barium titanate particles by injecting a raw material containing a barium titanate compound into a high-temperature field heated to a temperature equal to or higher than the melting point of the compound; A step b of washing the powder containing the barium titanate-based particles formed in the step a, or calcining the powder containing the barium titanate-based particles formed in the step a and then washing the calcined powder; and step c) of firing the washed powder obtained through step b).

2. The method further includes a step d of classifying the powder containing barium titanate-based particles formed in the step a to obtain a plurality of powders having different average particle sizes, In the step (b), the powder particles obtained in the step (d) have an average particle size of 3.0 to 5.0 μm and a true specific gravity of 5.60 to 5.90 g / cm. 3 The method for producing a barium titanate-based powder according to claim 1 , wherein a powder represented by the formula (I) is used as the powder containing barium titanate-based particles formed in the step (a).

3. The method further includes a step d of classifying the powder containing barium titanate-based particles formed in the step a to obtain a plurality of powders having different average particle sizes, In the step (b), the powder particles obtained in the step (d) have an average particle size of 9.0 to 12.0 μm and a true specific gravity of 5.60 to 5.90 g / cm 3 The method for producing a barium titanate-based powder according to claim 1 , wherein a powder represented by the formula (I) is used as the powder containing barium titanate-based particles formed in the step (a).

4. The method for producing a barium titanate-based powder according to any one of claims 1 to 3, wherein in the step b, the powder containing the barium titanate-based particles formed in the step a is fired, and then the fired powder is washed.

5. A powder containing barium titanate particles, The barium titanate-based particle has a hollow area ratio of 5.0% or less in a cross section, A barium titanate-based powder, in which when 30 g of the powder is mixed with 142.5 mL of ion-exchanged water having an electrical conductivity of 1 μS / cm or less, and 7.5 mL of ethanol having a purity of 99.5% or more, shaken for 10 minutes, and then allowed to stand for 30 minutes to prepare an extract, the extract has an electrical conductivity of 200 μS / cm or less.

6. The barium titanate powder according to claim 5, having an average particle size of 3.0 to 12.0 μm.

7. The barium titanate powder according to claim 5, having an average sphericity of 0.80 or more.

8. The average particle size is 3.0 to 5.0 μm, and the BET specific surface area is 0.60 to 0.70 m 2 The barium titanate powder according to claim 5, wherein the molecular weight of the barium titanate powder is 1000 or more.

9. The average particle size is 6.0 to 8.0 μm, and the BET specific surface area is 0.40 to 0.50 m 2 The barium titanate powder according to claim 5, wherein the molecular weight of the barium titanate powder is 1000 or more.

10. The average particle size is 9.0 to 12.0 μm, and the BET specific surface area is 0.25 to 0.30 m 2 The barium titanate powder according to claim 5, wherein the molecular weight of the barium titanate powder is 1000 or more.

11. A filler for an encapsulant, comprising the barium titanate powder according to any one of claims 5 to 10.

Citation Information

Patent Citations

  • Single crystal ceramic particle and spherical oxide powder

    JP2005112665A

  • Dielectric powder

    JP2011102225A

  • Barium titanate powder, method for manufacturing barium titanate powder, and ceramic electronic component using the same

    JP2012211058A

  • Barium titanate powder and process for producing the same and use therefor

    JP2017024925A

  • High-purity barium titanate powder, method for producing same, resin composition, and fingerprint sensor

    WO2017217235A1